INFLUENCE OF GRAIN APHID PEST ON EXTERNAL WHEAT SYMPTOMS (American Journal of Technology and Applied Sciences, 2024)
According to the research in the article, it is indicated at what stage measures should be taken to protect plants from pests, given that aphids cause more damage to the tillering of wheat in grain fields.